2011
DOI: 10.1016/j.bbabio.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Homologous protein subunits from Escherichia coli NADH:quinone oxidoreductase can functionally replace MrpA and MrpD in Bacillus subtilis

Abstract: The complex I subunits NuoL, NuoM and NuoN are homologous to two proteins, MrpA and MrpD, from one particular class of Na+/H+ antiporters. In many bacteria MrpA and MrpD are encoded by an operon comprising 6-7 conserved genes. In complex I these protein subunits are prime candidates for harboring important parts of the proton pumping machinery. Deletion of either mrpA or mrpD from the Bacillus subtilis chromosome resulted in a Na+ and pH sensitive growth phenotype. The deletion strains could be complemented in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
27
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 51 publications
6
27
1
Order By: Relevance
“…Indeed, it has been proposed that MrpA channels Na ϩ , whereas MrpD channels H ϩ in the complex from B. subtilis (21). The results obtained with methanol-grown M. acetivorans indicated that the Mrp complex is not required for pH homoeostasis or tolerance to Na ϩ stress.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Indeed, it has been proposed that MrpA channels Na ϩ , whereas MrpD channels H ϩ in the complex from B. subtilis (21). The results obtained with methanol-grown M. acetivorans indicated that the Mrp complex is not required for pH homoeostasis or tolerance to Na ϩ stress.…”
Section: Discussionsupporting
confidence: 52%
“…Roles for Mrp of M. acetivorans of the domain Archaea were addressed by comparing growth parameters of the wild type versus the ⌬mrpA mutant cultured with either methanol or acetate. The MrpA subunit of the Mrp complex was targeted, since it had been shown that the homologous MrpA of Bacillus subtilis is essential for Na ϩ /H ϩ exchange activity and the proposed site of Na ϩ translocation (21,34,35). Figure 1 shows similar growth rates and final optical densities between the wild type and mutant grown with methanol, although the lag phase for both strains was lengthened when cultured at pH 8.0 compared to pH 6.8, indicating a required adaptation period for optimal growth at the higher pH for both the mutant and wild type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional similarity of MrpA to NuoL and that of MrpD to NuoN was recently corroborated by complementation studies using B. subtilis MrpA and MrpD deletions strains, in which the subunits of complex I could replace those of the Mrp antiporter (43). These observations further support the antiporter activity by complex I.…”
Section: Complex I With Na 1 /H 1 Antiporter Activitymentioning
confidence: 69%
“…The seven-subunit MrpABCDEFG complexes from Bacillus species have been model systems for investigation, with a focus on the MrpA and MrpD subunits that contain transmembrane acidic residues, consistent with ion translocation functions (24). Although MrpA and MrpD subunits from the domain Bacteria are implicated in translocation of Na ϩ and H ϩ , respectively, a consensus has emerged that all seven subunits are required for antiport activity (2,3,11,20,25,26). Specifically, expression of an MrpAD subcomplex in the antiporterdeficient Escherichia coli strain KNabc showed no antiport activity (27).…”
mentioning
confidence: 99%